COVID-19 experiences and fears among nurses: - Kavuran, Esin (Obzornik zdravstvene nege, 2025)
Introduction: COVID-19 has profoundly affected people's physical and mental health. Nurses, a crucial part of the healthcare workforce, face considerable anxiety due to the risk of infection. The aim of this study was to examine the relationship between COVID-19 fear levels among infected and non-infected nurses and to identify the influencing factors.Methods: For this cross-sectional study, data were collected through an online survey from 20 to 27 December 2020. A total of 281 nurses in Turkey participated, of whom 95 were COVID-19-positive and 186 were COVID-negative. Data were collected using the Fear of COVID-19 Scale. Descriptive statistics, Kolmogorov-Smirnov test, one-way ANOVA, Mann-Whitney U, and Kruskal-Wallis tests were used. Statistical significance was set at p < 0.05.Results: The sample consisted of 58.9% women and 41.1% men. Of the participants who tested positive, 42.1% had cared for COVID-19 patients on the night shift, compared to 35.5% of those who tested negative. Both groups reported using inadequate protective equipment. COVID-19-positive nurses reported an anxiety score of 22.89 (s = 8.97), while COVID-19-negative nurses reported an anxiety score of 21.10 (s = 7.11).Discussion and conclusion: Higher anxiety levels were observed among nurses who tested positive for COVID-19. These results emphasise the need for more support and resources for nurses. It is important to address nurses' anxiety and take appropriate measures, including reasonable shift schedules and psychological support.
Keywords: anksioznost; anxiety; koronavirusna bolezen; kvantitativna raziskava; nursing; perception; quantitative study; SARS Coronavirus 2 infection; zaznava; zdravstvena nega